Biodegradable foams based on cassava starch, sunflower proteins and cellulose fibers obtained by a baking process - Salgado, Pablo Rodrigo (2008)
Biodegradable food packaging trays made from cassava starch, sunflower proteins and cellulose fibers were obtained by a foam baking process. The effect of varying the proportions of these three components on physico-chemical and mechanical properties of the trays was studied, as was the relationship between these properties and the trays' microstructure. All trays presented thicknesses between 1.55 and 1.76 mm, and densities between 0.46-0.59 g/cm3. The increment of fiber concentration from 10 to 20 % w/w improved the mechanical properties and slightly reduced the post-pressing moisture content, but increased the water absorption capacity of the material in at least 15 %. The addition of sunflower proteins till 20% w/w reduced significantly the post-pressing moisture content (ca. 5.7%), the water absorption capacity (till 43 %) and the relative deformation of the trays (till 21%). The formulation presenting the best properties contained 20% fiber and 10% protein isolate, and had a maximal resistance of 6.57 MPa and a 38% reduction in water absorption capacity, corresponding to a more compact, homogeneous and dense microstructure.